Energy Efficiency of Binder Application in Concrete - Vinnichenko, Varvara; Ryazanov, Alexander (International Journal of Engineering and Technology, 2018)
Theoretical calculation of the thermal effect of formation of minerals of binders is carried out. The dependence allowing calculating the thermal effect of formation of minerals of lime, gypsum, slag cement, portland cement, dolomite cement is presented. The formula also takes into account the effect of organic components in the mixture. A comparative analysis of the energy efficiency of different types of binder in concrete is carried out. It is shown that the use of slag cement in the production of concrete mix is twice as effective as portland cement. This is due to the presence in the slag of calcium oxide, which does not need energy to carry out the endothermic decarbonization reaction. Lime in the concrete composition has a rate of energy consumption is five times greater. This means, industrial waste which contains calcium oxide (slag, ash and others) can replace natural materials with high efficiency.Â Â